Comparative Analysis of Legal Recourses for Document Forgery in Civil Law: Indonesia and ASEAN Countries - Hussy, Maharani Millenia; Tjempaka, Tjempaka (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The practice of document forgery in civil transactions, often aiming to unjustly benefit one party over another, is a significant concern in many jurisdictions. This necessitates effective civil legal resources for the aggrieved parties to claim redress and compensation. In Indonesia, the approach to legal remedies is bifurcated into preventive and repressive measures, with the former encompassing legal provisions against document forgery and the latter involving the pursuit of civil litigation, as exemplified by cases such as the one adjudicated in Case Number 55/Pdt.G/2021/PnKpn by the Kepanjen District Court in East Java. This research aims to critically examine the civil legal remedies available in Indonesia for cases of document forgery, using the case as a focal point, and to contrast these with the corresponding legal frameworks in other ASEAN countries, including Malaysia, the Philippines, Brunei Darussalam, Singapore, Thailand, Vietnam, and Myanmar. The impetus for this comparative study stems from a recognized gap in the discourse surrounding document forgery within the civil law context. The methodology employed is normative legal research, involving an in-depth analysis of relevant civil codes and case law. This study’s findings highlight the nuances and effectiveness of legal resources against document forgery within these diverse legal systems, aligning with theories of legal protection.